Effect of microclimatic conditions on the reproductive behavior of the Helix aspersa - Fernández Cabrera, Hugo Ángel (2013)
The aim of this study was to evaluate the effect of microclimatic conditions (temperature and relative humidity) on the reproduction of land snails (Helix aspersa). For this, incubation’s chambers were conditioned with different four levels of relative humidity and temperature. Posture, length of incubation and hatching rate were evaluated. It was concluded that 81.0 ± 0.63% of relative humidity and 23.9 ± 0.39 °C of temperature the best results are achieved.